Plague circulation and population genetics of the reservoir Rattus rattus: the influence of topographic relief on the distribution of the disease within the Madagascan focus. - Carine Brouat; Soanandrasana Rahelinirina; Anne Loiseau; Lila Rahalison; Minoariso Rajerison; Dominique Laffly; Pascal Handschumacher; Jean-Marc Duplantier (Public Library of Science (PLoS), 2013)
BACKGROUND:Landscape may affect the distribution of infectious diseases by influencing the population density and dispersal of hosts and vectors. Plague (Yersinia pestis infection) is a highly virulent, re-emerging disease, the ecology of which has been scarcely studied in Africa. Human seroprevalence data for the major plague focus of Madagascar suggest that plague spreads heterogeneously across the landscape as a function of the relief. Plague is primarily a disease of rodents. We therefore investigated the relationship between disease distribution and the population genetic structure of the black rat, Rattus rattus, the main reservoir of plague in Madagascar. METHODOLOGY/PRINCIPAL FINDINGS:We conducted a comparative study of plague seroprevalence and genetic structure (15 microsatellite markers) in rat populations from four geographic areas differing in topology, each covering about 150-200 km(2) within the Madagascan plague focus. The seroprevalence levels in the rat populations mimicked those previously reported for humans. As expected, rat populations clearly displayed a more marked genetic structure with increasing relief. However, the relationship between seroprevalence data and genetic structure differs between areas, suggesting that plague distribution is not related everywhere to the effective dispersal of rats. CONCLUSIONS/SIGNIFICANCE:Genetic diversity estimates suggested that plague epizootics had only a weak impact on rat population sizes. In the highlands of Madagascar, plague dissemination cannot be accounted for solely by the effective dispersal of the reservoir. Human social activities may also be involved in spreading the disease in rat and human populations.